THE USE OF TOOLS DENSITOMETRY IN THE QUANTITATIVE COMPUTATIONS OF PROTEIN FRACTIONS - Natalia L. Vostrikova (Теория и практика переработки мяса)
In the study of proteomic profiles of proteins, many scientists stop at the stage of obtaining the final data of the experiment in the form of gels. They have got no information on the possibilities and prospects concerning the application of modern computer and bioinformatics resources that allow to convert the result from qualitative to quantitative form. The use of computer technology allowed to save the recorded images and carry out the calculations with chromatograms using digital video images.Densitometry with the use of video technology is characterized by high calculation speed and low cost of consumables. Digitally archived chromatograms may be used at any time for a number of applications including calculation.Thus, the “manual” bioinformatics analysis allows not only to use different densitometer software for conversion and storage of gels in digital form, but also to quantitatively interpret the results obtained.This paper presents the methods for practical application of bioinformatics tools in the interpretation of protein profiles obtained by one-dimensional and two-dimensional electrophoresis and converted into digital image. The aspects of the quantitative interpretation of electrophoretograms from one-dimensional electrophoresis (1DE) and two-dimensional electrophoresis (2DE) resulting from the studies of muscle tissue of farm animals are reviewed. Examples of various calculation software usage are given. The work in this direction will allow to considerably expand approaches for identification and quantification of protein markers related to quality, functionality and safety of food raw materials and finished products and to carry out metrological examination of the results for confirmation of product compliance.